Efficacy of one‐stage surgical treatment and clinical features in patients with multiple pressure ulcers1. (5th February 2016) - Han, Hyun Ho; Choi, Eun Jeong; Choi, Jong Yun; Rhie, Jong Won
Abstract: Treating patients with multiple pressure ulcers is a very challenging task for physicians. However, there are very few reports on treatment protocols for multiple pressure ulcers and treatment outcomes. The authors have consistently treated multiple pressure ulcers in a one‐stage operation rather than a staged operation. We evaluated multiple pressure ulcers patients who underwent a one‐stage operation from 2007 to 2014. A comparison was made between 20 patients who underwent a one‐stage operation on 44 foci and 68 patients with a single focus. Though the results, we could conclude that one‐stage operation of multiple pressure ulcers was found to have a shorter recovery period and shorter hospitalization without a significant increase in complications.